ANALISIS ELABORATION LIKELIHOOD MODEL DALAM KALIMAT PERSUASI KAMPANYE PRESIDEN 2019 DI FACEBOOK - NFN Indrawati (Balai Bahasa Kalimatan Selatan, 2019)
Facebook is a tool for effective and efficient persuasion with fast time and relatively inexpensive cost for campaigns. This research aims to reveal some types of sentence persuasion, through the elaboration analysis of likelihood model on Facebook This research uses qualitative content analysis methods. Qualitative content analysis is a systematic analysis to analyze the content of messages and to process messages that can not be separated from the interests of the message maker. The data the authors take in this study is data contained on Facebook from February to April 2019. The Data in this study is a sentence that has a persuasion message on Facebook. The data sources used in this research are sourced from direct observation on social media Facebook which is then researcher Screenshoot. Data analysis is conducted through observation, grouping, identifying, analyzing data, and concluding research analysis results. Based on the results of the study, there are several types of persuasion sentences, namely: (1) A strong persuasion sentence, which is a strong persuasion sentence has an explicit call to action, usually accompanied by data and facts; (2) A neutral persuasion sentence, which is a persuasion sentence whose contents do not change our attitude or behavior to a friend who has a different choice than ours; (3) A weak persuasion sentence, i.e. a persuasion sentence done implicitly (expressed) or indirectly; and (4) A side persuasion sentence, which is a sentence influenced by things like the repetition of a highly credible spokesman to convince others.